Changes in Self-Reported Depressive Symptoms Among Adults in the United States From 2005 to 2016. (March 2021) - Kauffman, Kelley; Horvat Davey, Christine; Dolata, Jacqueline; Figueroa, Maria; Gunzler, Douglas; Huml, Anne; Pencak, Julie; Sajatovic, Martha; Sehgal, Ashwini R.
BACKGROUND: This study examined interview data from the National Health and Nutrition Examination Survey from 2005 to 2016.AIM: To determine national trends in self-reported depressive symptoms.METHOD: Depressive symptoms were assessed using self-reported data on the nine-item Patient Health Questionnaire (PHQ-9), with a total score ≥10 and an individual item score of 2 or 3, indicating greater severity.RESULTS: A total of 31, 191 individuals contributed PHQ-9 data from 2005 to 2016. The absolute proportion of individuals with total PHQ-9 score ≥10 increased from 6.2% to 8.1%. After adjustment for participant demographic characteristics and comorbid conditions, the odds ratio for high PHQ-9 score at the end versus the beginning of the study interval was 1.27 (95% confidence interval [CI: 1.07, 1.50]). Anhedonia, guilt/worthlessness, appetite, and hypoactivity/hyperactivity had the largest increases in individual item risk after adjusting for demographic and comorbid characteristics.CONCLUSIONS: There were sizeable increases in the prevalence of self-reported depressive symptoms in the United States over an 11-year period. Further work is needed to understand the reasons for and implications of this increase. However, the results suggest greater efforts should be made by health care providers to screen for depressive symptoms that may warrant further assessment, treatment, or referral to mental health services as needed.